An alternative approach to mobility analysis in vehicular ad hoc networks - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2016)
Understanding vehicle mobility is essential for devising successful protocols for vehicular communications. Vehicles move at varying speeds on roads whose complexities range from plain highway lanes to urban boulevards with intersections/circles, traffic lights and various points of interest on them. This mobility pattern combined with vehicle density fluctuations depending on location and time makes understanding the vehicular mobility a challenging task and leads to vehicular communication solutions which are incomplete or low-performance. In this paper, we propose an alternative method for vehicular mobility analysis. We attempt to extract the spatio-temporal vehicular mobility characteristics of large, complex geographical areas by dividing them into cells and analyzing on these cells certain metrics that are of interest for vehicular communication. We first discuss the logic behind our approach. We then present definitions of the metrics used by the proposed analysis method. We conclude with a demonstration of the results achieved when the proposed method is applied in the analysis of a large scale mobility trace. © 2016 IEEE.
Keywords: Mobility; Mobility Analysis; VANET; Vehicular Networks